Outcomes in children with vesicoureteral reflux receiving antibiotic prophylaxis - Madeline G Tompkins; Michelle Kussin; John C Christenson; LaKeisha Boyd; Kiet Tat; Jack G Schneider; Rachel T Han (Antimicrobial Stewardship & Healthcare Epidemiology)
Antibiotic prophylaxis in children with vesicoureteral reflux (VUR) remains controversial. We reviewed patients diagnosed with VUR after an index urinary tract infection (UTI) who subsequently received antibiotic prophylaxis. Recurrent UTIs in patients with and without urologic anomalies occurred in 57% and 33%, respectively. Multidrug-resistant organisms accounted for 25% of first UTI recurrences.